2004
DOI: 10.1242/jcs.01238
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatin andtri-methylated lysine 20 of histone H4 in animals

Abstract: Tri-methylated lysine 20 on histone H4 (Me(3)K20H4) is a marker of constitutive heterochromatin in murine interphase and metaphase cells. Heterochromatin marked by Me(3)K20H4 replicates late during S phase of the cell cycle. Serum starvation increases the number of cells that exhibit high levels of Me(3)K20H4 at constitutive heterochromatin. Me(3)K20H4 is also present at the centromeric heterochromatin of most meiotic chromosomes during spermatogenesis and at the pseudoautosomal region, as well as at some telo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
181
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(194 citation statements)
references
References 51 publications
11
181
0
1
Order By: Relevance
“…Emerging evidence provided links between histone H4-Lys 20 trimethylation and oncotransformation (24,30,46,47). Interestingly, Fraga et al (24) have observed a decrease in trimethylated histone H4-Lys 20 in leukemia cell lines when compared with normal lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence provided links between histone H4-Lys 20 trimethylation and oncotransformation (24,30,46,47). Interestingly, Fraga et al (24) have observed a decrease in trimethylated histone H4-Lys 20 in leukemia cell lines when compared with normal lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that loss of histone H4-Lys 20 trimethylation could result in a more ''relaxed'' heterochromatin organization, which markedly impairs genome stability and viability of the cells (46,47) and may lead to the malignant transformation (24).…”
Section: Radiation-induced Changes In Histone H4-lys 20 Trimethylationmentioning
confidence: 99%
“…4E). (31) In addition, H4-K20 can be monomethylated or trimethylated by the HMTs PR-Set7 (21,32) and Suv4-20h1/2 (33) respectively (Fig. 4F,G).…”
Section: Histone Methyltransferasesmentioning
confidence: 99%
“…(21,26,32) However, the mechanisms behind this so-called ''epigenetic crosstalk'' have yet to be fully determined. Histone methylation could also be more of a lasting covalent modification than histone deacetylation.…”
Section: Histone Methyltransferasesmentioning
confidence: 99%
“…This reduces autophagy, thereby providing a feedback mechanism to control the amount of autophagy [17]. Furthermore, global changes in H4K20me3 [19], H3K4me3 [17], and H3K56ac [20] have been associated with autophagy induction, but whether and how this affects autophagy remains to be determined [17,19,20]. Importantly, extensive studies which assess and combine genome-wide transcriptomic and epigenomic events underlying autophagy are lacking.…”
Section: Introductionmentioning
confidence: 99%